Effect of different freeze drying cycle in Semimembranous and Gluteus Medius bovine muscles: changes on microstructure, colour, texture and physicochemical parameters - Messina, Valeria (2016)
The aim of the present research was to evaluate effects of freeze drying cycle in Semimembranous and Gluteus Medius bovine muscles (sp: Aberdeen Angus) for instant meal. Samples were analysed by Scanning electron microscopy; texture and colour parameters were analysed by image analysis and physicochemical properties by instrumental assays. Micrographs revealed that a higher porous size structure and shrinkage of muscle fibre diameter were obtained at −40 °C. In Semimembranous and Gluteus Medius bovine muscles, significant difference (P < 0.0001) was obtained for texture, colour and physicochemical parameters. Results revealed that colour, texture and physicochemical parameters were less affected when freeze drying cycle was performed at −40 °C. Freeze drying cycle at −50 and −60 °C showed increases in lightness (L*) and yellowness (b*); decrease in redness (a*) and in water absorbing capability).